Geographic Information System - Modern Teaching Method in Business Administration - Irina Albăstroiu; Mihai Felea; Cristinel Vasiliu (Amfiteatru Economic Journal, 2014)
The evolution of information and communication technologies has made possible the use of new ways of teaching and learning. Geographic Information System (GIS), one of these new technologies, allows a visual learning environment, facilitates active learning and spatial thinking, and also improves students' skills on using information technologies. The aim of this paper is to examine how GIS applications contribute to the education field but also to present the limitations of their use in the teaching process. Also, we intend to present issues associated with their use in the business administration field. In our approach regarding the modernization of teaching methods in business administration, we conducted an exploratory research using a standard questionnaire-based methodology to identify the opinions of teachers from the Academy of Economic Studies (AES) regarding the introduction of GIS subjects and applications in business administration study programs.
Keywords: O33; L86; I25; 330; Geographic Information System (GIS); teaching method; business administration; education